FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA ACCOUNT REPRESENTATIVE DI KPP PRATAMA GIANYAR, TABANAN, DAN SINGARAJA - Yobi, Ni Made Dwi Juni; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi, 2017)
The government of Indonesia, one of developing countries, has been developing intensively in national context in order to be developed country which brings prosperity to Indonesian people. One of the main constraints regarding the national development is financial problem so that the government always makes the effort to increase the country's income. Tax is one of the most potential income source which plays important role in national development. In spite of that, the people's awareness to pay tax is still low so that the government determines several policies to increase tax income. The implementation of modernized administrative tax system has been an innovation to increase the tax service. The quality of it is considered to increase the tax compliance. The quality of tax service is affected by the performance of tax officers, especially the Account Representatives. Because of this, influential factors affecting their performance should be considered. The study aimed to find out the influence of training, motivation, professionalism and organizational commitment on performance of AR working at KPP Pratama (small tax office) Gianyar, Tabanan & Singaraja. All 61 AR working at KPP Pratama Gianyar, Tabanan & Singaraja had been chosen as the respondents of this research. Sample was determined using saturation sampling technique & the data were analyzed using multiple linear regression. The research proved that training (X1), motivation (X2), professionalism (X3), organizational commitment (X4) significantly affect AR's performance with the adjusted R-square value 80%.
Keywords: tax, performance, Account Representative